Rigorous Solution to Plane Wave Scattering by an Arbitrary-Shaped Particle Embedded into a Cylindrical Cell of Similar Material - Constantine A. Valagiannopoulos (International Journal of Antennas and Propagation)
An infinite cylinder of arbitrary shape is embedded into a circular one, and the whole structure is illuminated by a plane wave. The electromagnetic scattering problem is solved rigorously under the condition that the materials of the two cylinders possess similar characteristics. The solution is based on a linear Taylor expansion of the scattering integral formula which can be useful in a variety of different configurations. For the specific structure, its own far field response is given in the form of a double series incorporating hypergeometric functions. The results are in good agreement with those obtained via eigenfunction expansion. Several numerical examples concerning various shape patterns are examined and discussed.